Community Social Capital in Fullfilment Child’s Rights of Women Migrant Workers in Soppeng District, South Sulawesi - Anggriani Syarif, Selvy; Sumarti, Titik; Sri Wahyuni, Ekawati (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2017)
ABSTRACTFulfillment child’s rights of women migrant workers is not only the parents responsibility, but communities responsibility as well.The presence of community in parenting is presumed to support the fulfillment child’s rights of women migrant workers. This research aims to describe fulfillment of child’s rights of women migrant workers in Soppeng district and analyze the social capital in community that affect to the fulfillment of child’s rights of women migrant workers. This study which uses mixed-method by combining qualitative and quantitative approaches. There are five child’s right that must be fulfilled, are the right to civil and freedom, the right to family and alternative parenting, the right to health and welfare, the right to education,the use of leisure and cultural activities, and the right to special protection. The results show that some of child’s rightsare not properly fulfilled, particularly for boys in the right to civil and freedom and the right to family and alternative parenting. Even though it is not utilized well by family of women migrant workers, social capital of consummatory and instrumental in community possesses a significant role to encourage the parenting for child of women migrant workers that is undertaken by caregiver.Keywords: Social capital, child’s rights, parenting, women migrant workersABSTRAKPemenuhan hak dasar anak buruh migran perempuan tidak hanya menjadi tanggung jawab orang tua, tetapi juga komunitas. Kehadiran komunitas dalam pengasuhan dianggap memberikan dukungan terhadap pemenuhan hak dasar anak buruh migran perempuan. Tujuan penelitian ini adalah mendeskripsikan pemenuhan hak dasar anak buruh migran perempuan di Kabupaten Soppeng dan menganalisis modal sosial dalam komunitas yang memengaruhi pemenuhan hak dasar anak buruh migran perempuan. Penelitian ini menggunakan pendekatan kuantitatif dan kualitatif. Terdapat lima hak dasar anak yang wajib dipenuhi, yaitu hak sipil dan kebebasan, hak lingkungan keluarga dan pengasuhan alternatif, hak kesehatan dasar dan kesejahteraan, hak pendidikan, pemanfaatan waktu luang dan kegiatan seni budaya, serta hak perlindungan khusus. Hasil penelitian ini menunjukkan bahwa tidak semua hak dasar anak buruh migran perempuan terpenuhi dengan baik, khususnya bagi anak laki-laki. Modal sosial komunitas yang bersifat consummatory dan instrumental memiliki peran besar untuk mendukung pengasuhan yang dilakukan pengasuh pengganti bagi anak buruh migran perempuan, tetapi belum dimanfaatkan dengan baik oleh keluarga BMP.Kata kunci: Modal sosial, hak dasar anak, pengasuhan, buruh migran perempuan